CUSTODIAL DEATHS WITH RESPECT TO COMMUNICABLE DISEASES: A 5-YEARS RETROSPECTIVE ANALYSIS IN NORTH EASTERN DELHI - Meena, Mahesh Chand; Sellamuthu, Hariraj; Kumar, Mahesh; Bansal, Mukesh Kumar; Verma, S K (Journal of Forensic Medicine and Toxicology, 2025)
Background: Infectious diseases continue to pose a significant threat to public health, particularly indeveloping nations like India. Communicable diseases, better-known as infectious diseases, are illnesses caused by microorganismsthat can be transmitted from person to personparticularly, affecting the most vulnerable members of society such that the person under the custody, where limitation may arise even for the fundamental rights such as that right to health. Objectives: To determine the pattern of the communicable diseases common among the person in custody, leading to contagious infection and death which were autopsied in northeast region of Delhi. Methods: To find the trend, a retrospective autopsy-based study on communicable disease prevalence in Northeast Delhi region for duration of five years (2019 to 2023).
Keywords: Custodial death; Communicable diseases; Contagious diseases; Infectious diseases